Репродуктивные характеристики крымскотатарских женщин - Мустафаева, Л.А.; Козак, Н.А. (Фактори експериментальної еволюції організмів, 2014)
Aims. Reproductive behavior of women largely depends on cultural traditions and differs in representatives of various ethnic groups. Multinational population of Ukraine has been scarcely researched. The purpose of this research is to study the reproductive characteristics of Crimean Tatar women. Methods. 200 women aged 45–90 have been examined. In the research the number of pregnancies, medical and spontaneous abortions ectopic pregnancies, stillbirths and live births have been found out. According to the listed indicators the women of the southern, steppe and mountain subethnoses were compared and also Crimean Tatar and Slavic women. Results. The average number of pregnancies among Crimean Tatar women– 3.6, abortions – 0.9, spontaneous abortions – 0.3, ectopic pregnancies – 0.04, stillbirths – 0.1, live births – 2.6. Conclusions. For the Crimean Tatar people characteristically enlarged reproduction of the population.

Key words: Crimean Tatar, reproductive characteristics.